Social Assistance Receipt among Young Adults Grown up in Different Neighbourhoods of Metropolitan Sweden - Björn Anders Gustafsson; Katarina Katz; Torun Österberg (Institute of Labor Economics (IZA), 2020)
Using large samples of persons born in 1985 we investigate the relationship between characteristics of the neighbourhood where young people lived as adolescents and the probability that they will receive social assistance when aged 19, 20, and 21, for the three Swedish metropolitan regions - Stockholm, Gothenburg and Malmö. We estimated logistic regressions separately for the majority population and "visible immigrants" and included several characteristics of the neighbourhood and of the parental home in the specification. The probability of social assistance receipt as a young adult is strongly positively linked to social assistance receipt in the parental home and to several other factors. The major result is that the association with social assistance receipt in the neighbourhood where a person lived at age 16 remains strong when parental receipt and a number of other neighbourhood characteristics are controlled for. We conclude that measures to increase the education qualifications and various efforts to create jobs for young adults have a potential of decrease social assistance receipt among young adults. In addition there is also room for spatially focused measures aiming to reduce residential segregation and the demand for social assistance in locations with a comparably high rate of social assistance receipt.
Keywords: I38; J15; R23; 330; young adults; immigrants; neighbourhoods; Sweden; social assistance